Bibframe and the March hare - Agenjo-Bullón, Xavier; Hernández-Carrascal, Francisca (Anuario ThinkEPI, 2024)
The state of Bibframe implementation in 2023 is described based on the evolution of its main aspects, cataloging, and web-based information retrieval. Reference is made to issues arising from the correlation of Bibframe with RDA; the development of profiles, extensions, and variants of the model and their influence on Bibframe/RDF description exchange; the status of Bibframe editors for entity-based cataloging; and the technological contributions of library management systems, whether commercial or open, to adapt to Bibframe. The design and development of web interfaces for searching and discovery bibliographic data based on Bibframe are analyzed; and finally, some solutions are outlined for bibliographic data to be available for use on the general web, beyond the library community, as linked open data.